Perancangan dan Implementasi Sistem Persediaan Suku Cadang di Bengkel Menggunakan Metode Always Better Control - Dimas Putra Mahardika; Luvia Friska Narulita (Jurnal Rekayasa Sistem Informasi dan Teknologi, 2024)
XYZ is a private workshop that provides car services. In this workshop, the process of recording customer data and tracking the inflow and outflow of spare parts is still done manually using Microsoft Excel, resulting in poorly organized data. This can lead to the loss of customer data, mechanics being unaware of the services they need to perform, and discrepancies between the stock of spare parts in the warehouse and the recorded data. These issues can cause financial losses for the workshop. Therefore, a system is needed to effectively control the inventory in the workshop's warehouse. This research aims to design a control system using the ABC (Always Better Control) method. Implementing this method in the control system will assist the management in making decisions regarding all processes in the workshop. Based on testing using the black-box approach, it was found that the functions of the system features are working as expected. Additionally, testing using the SUS (System Usability Scale) approach resulted in an average score of 87.5, indicating that the system has been well-implemented.